2022
DOI: 10.1371/journal.pone.0265506
|View full text |Cite
|
Sign up to set email alerts
|

The role of collegiality in academic review, promotion, and tenure

Abstract: Review, promotion, and tenure (RPT) processes at universities typically assess candidates along three dimensions: research, teaching, and service. In recent years, some have argued for the inclusion of a controversial fourth criterion: collegiality. While collegiality plays a role in the morale and effectiveness of academic departments, it is amorphic and difficult to assess, and could be misused to stifle dissent or enforce homogeneity. Despite this, some institutions have opted to include this additional ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…• Mentorship: Activities from more experienced researchers to provide influence, guidance, or direction to assist or advise more junior colleagues (including research students, institutional colleagues, academic peers) in their personal and professional growth (Macfarlane 2007). • Collegiality: An underdetermined concept (Dawson et al 2022) implying respect, shared responsibilities and/or collaborative manners of interaction within community or institutional frameworks (Cipriano & Buller 2012;Dawson et al 2022;Haviland et al 2017) • Evaluation and curation: Activities supporting the improvement, quality assurance, selection and curation of the research work of others, including conference organisation, publishing editorial activities, and peer review (e.g., grant applications, publications and RPT applications).…”
Section: Research Citizenshipmentioning
confidence: 99%
See 2 more Smart Citations
“…• Mentorship: Activities from more experienced researchers to provide influence, guidance, or direction to assist or advise more junior colleagues (including research students, institutional colleagues, academic peers) in their personal and professional growth (Macfarlane 2007). • Collegiality: An underdetermined concept (Dawson et al 2022) implying respect, shared responsibilities and/or collaborative manners of interaction within community or institutional frameworks (Cipriano & Buller 2012;Dawson et al 2022;Haviland et al 2017) • Evaluation and curation: Activities supporting the improvement, quality assurance, selection and curation of the research work of others, including conference organisation, publishing editorial activities, and peer review (e.g., grant applications, publications and RPT applications).…”
Section: Research Citizenshipmentioning
confidence: 99%
“…As described in the introduction, collegiality has even been argued a "fourth criterion" alongside research, teaching and service (Hatfield & Cheek 2012). Dawson et al (2022) found that it plays "an important role in RPT processes, whether it is explicitly acknowledged in policies and guidelines or not". In our survey, the disjunct for this element (3rd highest overall) between respondents' own views (3rd most important) and their perceptions of institutional policies (13th most important) is hence especially interesting as it runs somewhat counter to previous studies.…”
Section: Research Citizenshipmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, calls for reforming assessment practices have extended to emphasize values promoted by parallel reform agendas including movements for open science, research integrity, and diversity, equity and inclusion (Curry et al, 2022). These movements share concerns that excessive emphasis on quantitative research performance indicators overlooks and dis-incentivizes other important academic contributions, including teaching (Geschwind and Broström, 2015), collegiality (Dawson et al, 2022), openness (UNESCO, 2021) and integrity (Bouter, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The employee who initially accepts to work within a certain framework is not expected to criticize or complain about what is asked of him/her. Of course, those who have the upper hand take the advantage of the systems and frameworks and interpret them according to their understanding and visions of the work (Dawson 2022 andNiehaus 2015 wrote on this topic), which deprives some employees of the benefits they need for the continuity of work, the avoidance of monotony and the competition with others in any company or institution, and as part of rewarding those distinguished employees in the field.…”
Section: Introductionmentioning
confidence: 99%